STUDI SOSIAL EKONOMI PENGRAJIN KERIPIK TEMPE DI KANAGARIAN SUNGAI LANGKOK KECAMATAN TIUMANG KABUPATEN DHARMASRAYA - Septiana, Reflia - (Pendidikan Geografi, 2014)
This study aimed to obtain the data, process, analyze and discuss the socio-economic study community artisans tempeh chips at kanagarian langkok river tiumang districts dharmasraya. in view of the: 1) social relationships, 2) Work experience, 3) capital, 4) Raw material , 5) Facilities and infrastructure, 6) Marketing, 7) Income. This study pertained to a descriptive study. The study population was all artisans tempeh chips, available in the District Tiumang Kenagarian Langkok River Dharmasraya. The research sample with total sampling of the population in the study area, totaling 63 samples craftsmen tempeh chips. Collecting data using guided questionnaires, statistical analysis used is descriptive by using a percentage formula. The results showed: 1) social relations craftsmen tempeh chips in Kenagarian Langkok River District of Tiumang Dharmasraya excellent craftsmen in general have never had a disagreement with a fellow craftsman, 2) Work experience in Kengarian craftsmen tempeh crisps Langkok River District of Tiumang Dharmasraya generally 5 years length of service, 3) a modal used for the production of tempeh crisps business in the District Tiumang Kenagarian Langkok River Dharmasraya generally be from their own savings, 4) Raw materials used in Kenagarian craftsmen tempeh crisps Langkok River District of Tiumang Dharmasraya generally have a high quality, 5) Facilities and infrastructure in the manufacture of tempeh crisps Kenagarian Langkok River District Subdistrict Tiumang Dharmasrya generally used has good quality, 6) Marketing results in the production of tempeh crisps Kenagarian Langkok River District of Tiumang Dharmasraya generally marketed in the district, 7) community income level craftsmen tempeh chips in Kenagarian Langk